Implementation of Diabetes Mellitus Minimum Service Standards at Pekanbaru City Public Health Center: A Qualitative Study - Putri, Intan Hardian; Jati, Sutopo Patria; Martini, Martini (Journal of Public Health for Tropical and Coastal Region, 2024)
Introduction: Minimum service standards in the health sector, one of which is Diabetes Mellitus (DM). The achievement rate of minimum service standards for diabetes mellitus in Pekanbaru City in 2020 is 38.05% of the target set at 100%.Purpose: This study aims to analyze the implementation of the minimum service standard policy of Diabetes Mellitus service indicators at the PHC in Pekanbaru City AreaMethod: The method used in this study is a qualitative method with a descriptive approach and data collection using interview techniques (in-depth interview) conducted on the heads of Public Health Center (PHC), health workers, and Non-Communicable Disease (NCD) program stakeholders in 4 PHC in Pekanbaru City and stakeholders of the Non-communicable Disease Control and Eradication Program of the Pekanbaru City Health Office.Result: The results of this study show that the minimum service standard target in the health sector has not been achieved in the diabetes mellitus indicator from 6 research indicators consisting of policy standards and objectives, resources, characteristics of implementing organizations, communication between organizations, attitudes of implementers, and environmental, social and political are still found obstacles that hinder the pace of achievement of the target of minimum diabetes mellitus service standards in Pekanbaru CityConclusion:  The Pekanbaru City Health Office and the Pekanbaru City PHC have implemented the policy of minimum service standards for diabetes mellitus indicators quite well. The achievement of minimum service standards in each PHC has not reached the number set by the government of the Pekanbaru City Health Office. This is because there are still several obstacles in the implementation of minimum health service standards on diabetes mellitus indicators.